Risk factors during pregnancy and birth‐related complications in HIV‐positive versus HIV‐negative women in Denmark, 2002–2014. Issue 2 (11th October 2019) - Ørbæk, M; Thorsteinsson, K; Moseholm Larsen, E; Katzenstein, TL; Storgaard, M; Johansen, IS; Pedersen, G; Bach, D; Helleberg, M; Weis, N; Lebech, A‐M
Abstract : Objectives: We aimed to compare risk factors for adverse pregnancy outcomes in women living with HIV (WLWH) with those in women of the general population (WGP) in Denmark. Further, we estimated risk of pregnancy‐ or birth‐related complications. Methods: A retrospective cohort study including all WLWH who delivered a live‐born child from 2002 to 2014 and WGP, matched by origin, age, year and parity, was carried out. We compared risk factors during pregnancy and estimated risk of pregnancy‐ and birth‐related complications using multivariate logistic regression. Results: A total of 2334 pregnancies in 304 WLWH and 1945 WGP were included in the study. WLWH had more risk factors present than WGP during pregnancy: previous caesarean section (CS) (24.7% versus 16.3%, respectively; P =  0.0001), smoking (14.2% versus 7.5%, respectively; P =  0.0001) and previous perinatal/neonatal death (2.3% versus 0.9%, respectively; P  =   0.03). We found no difference between groups regarding gestational diabetes, hypertensive disorders, low birth weights or premature delivery. More children of WLWH had intrauterine growth retardation (IUGR) [adjusted odds ratio (aOR) 1.9; 95% confidence interval (CI) 1.1–3.2; P =  0.02]. Median gestational age and birth weight were lower in children born to WLWH. WLWH had a higher risk of emergency CS (EmCS) (aOR 1.6; 95% CI 1.2–2.1; P =  0.0005) and postpartum haemorrhage (aOR 1.4; 95% CI 1.0–1.9; P =  0.02) but not infection, amniotomy, failure to progress, low activity‐pulse‐grimace‐appearance‐respiration (APGAR) score or signs of asphyxia. Conclusions: WLWH had more risk factors present during pregnancy, similar risks of most pregnancy‐ and birth‐related complications but a higher risk of postpartum haemorrhage and EmCS compared with WGP. Children born to WLWH had lower median birth weights and gestational ages and were at higher risk of IUGR.